2011
DOI: 10.1257/aer.101.2.991
|View full text |Cite
|
Sign up to set email alerts
|

The Willingness to Pay—Willingness to Accept Gap, the “Endowment Effect,” Subject Misconceptions, and Experimental Procedures for Eliciting Valuations: Comment

Abstract: Plott and Zeiler (2005) report that the willingness-to-pay/willingness-to-accept disparity is absent for mugs in a particular experimental setting, designed to neutralize misconceptions about the procedures used to elicit valuations. This result has received sustained attention in the literature. However, other data from that same study, not published in that paper, exhibit a significant and persistent disparity when the same experimental procedures are applied to lotteries. We report new data confirming both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(73 citation statements)
references
References 28 publications
5
59
2
1
Order By: Relevance
“…The arguably most prominent account of this type is loss aversion (Kahneman et al, 1990), which posits that buyers and sellers differ in their sensitivity to the magnitude of an object's potential consequences (see below for details). Further, there is evidence in valuations of risky options that buyers and sellers differ in probability weighting (e.g., Brenner, Griffin, & Koehler, 2012), and some authors have highlighted the role of strategic misrepresentation (e.g., Heifetz & Segev, 2004;Isoni, Loomes, & Sugden, 2011;Plott & Zeiler, 2005, 2007. Finally, Yechiam and Hochman (2013a) have recently proposed a loss-attention account, according to which buyers and sellers may differ in the amount of attention they invest in a task.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The arguably most prominent account of this type is loss aversion (Kahneman et al, 1990), which posits that buyers and sellers differ in their sensitivity to the magnitude of an object's potential consequences (see below for details). Further, there is evidence in valuations of risky options that buyers and sellers differ in probability weighting (e.g., Brenner, Griffin, & Koehler, 2012), and some authors have highlighted the role of strategic misrepresentation (e.g., Heifetz & Segev, 2004;Isoni, Loomes, & Sugden, 2011;Plott & Zeiler, 2005, 2007. Finally, Yechiam and Hochman (2013a) have recently proposed a loss-attention account, according to which buyers and sellers may differ in the amount of attention they invest in a task.…”
mentioning
confidence: 99%
“…Although the seminal investigations on the endowment effect (e.g., Kahneman et al, 1990;Thaler, 1980) involved the valuation of consumer items such as mugs and pens, many subsequent studies have turned to monetary lotteries and found a robust endowment effect there as well (e.g., Birnbaum, Coffey, Mellers, & Weiss, 1992; Birnbaum & Zimmerman, 1998;Brenner et al, 2012;Casey, 1995;Isoni et al, 2011;Kachelmeier & Shehata, 1992;Peters, Slovic, & Gregory, 2003; for a meta-analysis, see Yechiam, Ashby, & Pachur, in press). In contrast to consumer items, an advantage of lotteries is that their attributes can be quantified precisely (which is important for the modeling) and that they also allow to test for buyer-seller differences in risk attitude.…”
mentioning
confidence: 99%
“…Such reversals may indicate that preferences are context dependent in a way that makes the elicited certainty equivalents induce a ranking which differs from preferences (Tversky et al 1988). This is still an area of active research (Loomes et al, 2010;Plott and Zeiler, 2005;Isoni et al, 2011).…”
Section: Experimental Tests 351 Preference Reversal Under Riskmentioning
confidence: 99%
“…In their carefully designed experiment, they try to ensure that participants fully understand the task they face and observe no significant WTP-WTA gap in a classic mug-trading experiment. However, Isoni et al (2011) show that for a specific kind of goods, i.e. lotteries, the asymmetry in evaluations is resilient to strict experimental procedures aimed at minimizing misconceptions.…”
Section: Introductionmentioning
confidence: 99%